Farm resilience: evidence from Kansas - Davtyan, Karen (Kansas State University, 2022)
The purpose of this study is to build on the findings of Lindbloom (2018) on the effect of diversification on farm resilience and expand the literature in two main ways. First, this study examines farm resilience over a larger time period including the most recent shocks related to the farm income decline of 2015 and the US-China trade war of 2018. Second, the empirical model is enhanced to include adaptive capabilities. Specific objectives include (i) measuring the resilience of Kansas agricultural producers at the individual farm level during four shocks in the 1980-2021 period, and (ii) estimating an enhanced empirical model to gain more insights on the effect of farm level resources and capabilities on a farm’s ability to withstand (buffering) and restructure (adaptive) during the exogenous shocks. The objectives will be achieved by adopting and extending the conceptual and analytical frameworks from Lindbloom (2018). The data for this research was obtained from the Kansas Farm Management Association (KFMA), which contains detailed farm-level financial and production information for farms in Kansas between 1973 and 2021. Resilience index values have been computed at the individual farm level for four shock periods using a similar approach as Lindbloom (2018). Regression analyses are conducted by conducting a fractional logit model. The main findings of the study indicate that the buffering capabilities identified in Lindbloom (2018) are generalizable across an expanded range of shocks. The results also indicate that in addition to diversification, crop inventory, and debt-to-asset ratio, the depreciation ratio serves as a buffering capability for the shocks during the period analyzed. Lastly, the results indicate that the presence of a non-linear relationship between a number of farm characteristics and farm resilience, implying that certain resources and capabilities can serve as buffering and adaptive capabilities up to a specific threshold beyond which their impact on resilience turns negative. This study extends the existing literature on farm resilience and provides an enhanced conceptual and analytical platform for future studies over extended time periods including COVID-19 and Russia-Ukraine conflict related shocks.
Keywords: Resilience; Kansas; Farm; Agriculture; Resilience triangle; Diversification